THE COMPETENCE BASED CURICULUM OF BIOLOGICAL EDUCATION’S UNDERGRADUATE PROGRAMS - Subali, Bambang (Bioedukasi: Jurnal Pendidikan Biologi, 2005)
This is the review which dealed with the curiculum of, both an educational study program generally and biological study program as well. The review showed the importance to set the curiculum up and fit it with the competence based curiculum, since that curiculum has been applied by the user, thus, it needed to response respectively.The first step is, indeed, setting up the curiculum of educational study program, becoming the competence based curiculum. That curiculum setting up by two main steps are defining the targeted output competence, followed by defining the competency for group of subjects and then for each subject. Secondly, is applying the curiculum in a daily educational proccesses, and then give it an assesment, evaluation and review toward the proccesses it self and the output respectively.The competence based curiculum could provide some output as a young teacher which has some competency. However, some certification test is still needed to filter the output and give rise to the high quality and full of competence teacher. After all, the user will prove it and give the feed back to us.This is the review which dealed with the curiculum of, both an educational study programgenerally and biological study program as well. The review showed the importance to set thecuriculum up and fit it with the competence based curiculum, since that curiculum has been applied bythe user, thus, it needed to response respectively.The first step is, indeed, setting up the curiculum of educational study program, becoming thecompetence based curiculum. That curiculum setting up by two main steps are defining the targetedoutput competence, followed by defining the competency for group of subjects and then for eachsubject. Secondly, is applying the curiculum in a daily educational proccesses, and then give it anassesment, evaluation and review toward the proccesses it self and the output respectively.The competence based curiculum could provide some output as a young teacher which has somecompetency. However, some certification test is still needed to filter the output and give rise to the highquality andfull of competence teacher. After all, the user will prove it and give the feed back to us.